(untitled) (Texas Journal of Medical Science, 2024)
Acute and chronic toxicity of lipid concentrate of Eryx snakes was studied on sexually mature white mice and rats. It was found that in experimental animals in the period after acute and chronic application of lipid concentrate of Eryx snakes there are no significant changes in anthropometric, biochemical, haematological and pathomorpholigical parameters, which allows to refer lipid concentrate of Eryx snakes to practically non-toxic compounds. The results of acute and chronic toxicity studies indicate the harmlessness of lipid concentrate of Eryx snakes.